Remittances and institutions : are remittances a curse? - Abdih, Yasser [et al.] (IMF [Washington]US, 2008)
Addresses the complex relationship between the receipt of workers' remittance and institutional quality in the recipient country. Shows how an increase in remittance inflows can lead to deterioration of institutional quality - specifically to an increase in the share of funds diverted by the government for its own purposes.